2017
DOI: 10.1164/rccm.201607-1404oc
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Pleural Fluid Drainage Frequency in Patients with Malignant Pleural Effusions. The ASAP Trial

Abstract: Among patients with malignant pleural effusion, daily drainage of pleural fluid via an indwelling pleural catheter led to a higher rate of autopleurodesis and faster time to liberty from catheter. Clinical trial registered with www.clinicaltrials.gov (NCT 00978939).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(148 citation statements)
references
References 19 publications
7
135
1
5
Order By: Relevance
“…However, our results show a lower rate of removal due to IPC-related spontaneous pleurodesis (32.2% overall: 33.1% in MPE group, 23.8% in non-MPE group) in line with the placebo arm of the ASAP trial which reported 24% rate of IPC-related spontaneous pleurodesis with standard IPC drainage [7]. Excluding patients with evidence of pleural infection at the time of IPC insertion, our results demonstrate significant infection rates of 8.6% (6.6% for pleural infections, 3.0% for soft tissue infections) over the period of follow-up, occurring late.…”
Section: Discussionsupporting
confidence: 79%
“…However, our results show a lower rate of removal due to IPC-related spontaneous pleurodesis (32.2% overall: 33.1% in MPE group, 23.8% in non-MPE group) in line with the placebo arm of the ASAP trial which reported 24% rate of IPC-related spontaneous pleurodesis with standard IPC drainage [7]. Excluding patients with evidence of pleural infection at the time of IPC insertion, our results demonstrate significant infection rates of 8.6% (6.6% for pleural infections, 3.0% for soft tissue infections) over the period of follow-up, occurring late.…”
Section: Discussionsupporting
confidence: 79%
“…In a recent randomized trial, Impact of Aggressive versus Standard Drainage Regimen Using a Long-Term Indwelling Pleural Catheter trial (ASAP trial), rates of spontaneous pleurodesis were higher in patients daily drainage compared to the every other day drainage of pleural fluid via a TPC (47% vs. 24%, respectively; P = 0.003). Median time to spontaneous pleurodesis was shorter in the daily drainage group (54 days) as compared with the every other day drainage (90 days) (80).…”
Section: Tunneled Pleural Catheter (Tpc)mentioning
confidence: 83%
“…Drainages and dressing changes were completed by nurses who have been trained on proper catheter care. When drainage quantity was decreased to less than 50 mL for 3 sequential drainage attempts, without evidence of reaccumulation of pleural fluid on chest X-ray, spontaneous pleurodesis was considered to have occurred and the IPC was removed [12,13,15].…”
Section: Methodsmentioning
confidence: 99%
“…Collected data have traditionally shown an overall rate of spontaneous pleurodesis and IPC removal of around 45% [13,14], although more recently published randomized control trial have demonstrated a rate of spontaneous pleurodesis closer to 25% in the control groups [12,15]. Identifying who will ultimately have their catheter removed is important from the perspective of the patient inquiring about IPC placement.…”
Section: For Editorial Comment See P 497mentioning
confidence: 99%